Penerapan Metode Linear Regression untuk Memprediksi Peserta Training pada PT. NetSolution - Nendi; Fatonah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Along with the rapid development of technology, the use of information technology is also very much needed by many companies as well as yourself. For this reason, many people have an interest in doing IT training, in addition to increasing knowledge, IT training is also good for improving careers. PT Netsolution is one of the companies that provides IT training services. In its business, it must have a very large set of training participant data, therefore the data must be processed properly and neatly. This research was conducted in order to help the Sales & Marketing team to predict the number of new training participants, so that the admin can prepare a training schedule that is predicted to increase in each year. In this case the Linear Regression method is a method that can help estimate or predict new training participants in the future. The software that will be used to apply the Linear Regression method is RapidMiner and produces Performance with an RMSE value of 0.503 which shows good performance and fairly accurate prediction results.